Infrastructure surveillance system for Dandemutande Investments - Manga, Kudakwashe Joe (Midlands State University, 2018)
Dandemutande Investments was face with a network management and tracking problem. The issues that were presented by old manual system include, missed service level agreement due to delayed response to network outages and incidences, the support team had to familiarize with several troubleshooting tools, manual compilation of system reports and the system was reactive and action to resolve network issues were only taken after the they had already occurred. The Infrastructure Surveillance System is an online solution that facilitates and simplifies real-time monitoring of systems and services availability. The Infrastructure Surveillance System monitors the availability and compute uptime of entities such as Base Transceiver Stations (BTS), Point of Presence (POPs), monitoring availability of given services running on specific ports on hosted servers in the Data Centre, monitor bandwidth utilization and latency, log the traffic data and create graphs. The system helps to secure and provide efficient means of carrying out interactive and adaptive infrastructure surveillance. After a feasibility study was carried out, it was deduced that though there are constraints involved, the benefits realized from setting up the new system outweigh the total cost incurred. The technical resources and operational logistics at the company’s disposal allowed for the new system to be developed. Interviews, questionnaires and observation where used as data gathering methodologies and it was found out that engineers have in the past had to go through a cumbersome and non-efficient manual process of identifying and resolving network related issues. The system was developed using C# programing language, Visual Studio 2017 and SQL Lite for the database. Unit testing, integration and acceptance testing was carried out on the system whereby the following where included, system security, verification and authentication, data validation and basic functionalities. Parallel changeover was implemented whereby the two systems were run concurrently to minimize risks associated with discarding the old system completely. It was recommended that further development be considered to include additional functionality by linking the infrastructure surveillance system to the billing system and introduce additional product offering through on-demand access were customers are only billed for the total time they were online and accessed the system.